Erosive Rainfall Thresholds for Five Typical Soils in Water Erosion Region of China - Wang Ying; Yang Yang; Liu Baoyuan; Liu Yingna (Shuitu baochi tongbao)
[Objective] The practical thresholds separating erosive from non-erosive rainfall events were determined to effectively reduce the workload of soil erosion prediction, and to provide references for regional soil erosion prevention. [Methods] Five bare fallow runoff plots packed with typical soils from five water erosion subregions of China were established in the Fangshan District of Beijing City. We used the rainfall erosivity deviation method to derive the two thresholds of rainfall amount (P) and maximum 30-minute rainfall intensity (I30) for each plot based on runoff and soil loss data obtained during 2006—2019. [Results] ① The I30 thresholds were more effective than the P thresholds in identifying erosive rainfall events. ② The erosive rainfall thresholds were highest for the black and cinnamon soil plots, both having P thresholds of 10.0 mm and I30 thresholds of 10.2 mm/h, followed by the loess plot with P and I30 thresholds of 9.5 mm and 8.9 mm/h, respectively. The thresholds were lower for the purple and red soil plots. The corresponding P thresholds were 5.4 and 6.1 mm, respectively, and the I30 thresholds were 3.2 and 5.2 mm/h, respectively. ③ To acquire reliable and stable thresholds, at least 12 years of runoff and soil loss monitoring data were required for each plot. [Conclusion] Erosive rainfall thresholds differed among soils in different regions due to differences in soil properties such as particle size distribution and organic matter content, as well as in local climate factors such as rainfall pattern.